Reactivity of Al-Cr microparticles for aluminizing purposes. (February 2017) - Grégoire, B.; Bonnet, G.; Pedraza, F.
Abstract: Despite the extensive use of Al-Cr mixtures to aluminize metal substrates, little is known on the reactivity between Al and Cr to control the aluminizing activity. In this work, Al and Cr reactivity was investigated by DSC from Al and Cr microparticles. The exothermic and endothermic reactions which occur upon heating mixtures of Al and Cr powders were identified. A highly exothermic reaction was observed for different Al-Cr compositions at a temperature of 637 ± 2 °C and was associated with the formation of Alx Cry intermetallic compounds. The intensity of this reaction (heat flow) was found to be dependent on the initial Al-Cr ratio. Three Al-Cr compositions were selected from DSC tests and literature for slurry aluminizing. These compositions were deposited by slurry on pure Ni substrate to investigate the role of Cr on aluminizing by comparison with a conventional simple Al slurry coating. The addition of Cr was found to decrease the Al activity on the surface by forming Alx Cry intermetallic compounds that limited the SHS reactions usually observed between Ni and Al during high-activity slurry processes. The synthesized Alx Cry intermetallic phases then behaved as masteralloys, for a single step aluminizing process at high temperature to promote the outward diffusion of Ni. Highlights: An exothermic reaction was identified by DSC mixing Al and Cr microparticles at 637 ± 2 °C (T < Tf (Al)). The exothermic reaction was associated with the formation of Alx Cry intermetallic compounds (IMCs) rich in Al. IMCs were probably formed through the peritectic transformations L + Al7 Cr → L + Al11 Cr2 → L + Al4 Cr. The addition of Cr in the Al-Cr slurry mixtures was found to decrease the Al activity through the formation of Alx Cry IMCs. The formation of Alx Cry phases hampered the inward diffusion of Al into the Ni substrate at low temperature (i.e. 650 °C).